2023
DOI: 10.3390/ijms24032384
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy as a Tool to Study the Pathophysiology of Brain Diseases

Abstract: The Raman phenomenon is based on the spontaneous inelastic scattering of light, which depends on the molecular characteristics of the dispersant. Therefore, Raman spectroscopy and imaging allow us to obtain direct information, in a label-free manner, from the chemical composition of the sample. Since it is well established that the development of many brain diseases is associated with biochemical alterations of the affected tissue, Raman spectroscopy and imaging have emerged as promising tools for the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…Numerous studies have addressed the capability of tissue identification by means of Raman spectroscopy [ 12 , 13 , 14 , 15 ]. These range from the basic task of identifying different anatomical areas of the brain to clinical diagnostic applications in the form of binary (between tumor tissue and healthy brain tissue) and multiclass (to determine distinct tumor entities) classifications [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have addressed the capability of tissue identification by means of Raman spectroscopy [ 12 , 13 , 14 , 15 ]. These range from the basic task of identifying different anatomical areas of the brain to clinical diagnostic applications in the form of binary (between tumor tissue and healthy brain tissue) and multiclass (to determine distinct tumor entities) classifications [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Still playing an important role in the structural characterization of substances, this method has significantly expanded the scope of application. Nowadays, it is used for early detection of cancer, 16 bacteria detection, 17 to study the pathophysiology of brain diseases, 18 to determine the biochemical composition of plant, 19 etc. It also demonstrates the possibility of working with complex samples (multicomponent mixtures), for example, a study reported the classification of blood samples obtained from 11 animal classes and human subjects by statistical analysis of their Raman spectra.…”
Section: Discussionmentioning
confidence: 99%
“…The Raman scattering phenomenon was first observed in 1928 by Sir Chandrasekhara Raman, leading to the development of the first Raman spectroscopy microscopes in the 1970s [28]. The Raman scattering phenomenon posits that the spontaneous inelastic scattering of light will occur based on the molecular characteristics of the sample [29,30]. Therefore, Raman spectroscopy allows for the rapid, non-destructive acquisition of label-free information directly from the sample's chemical characteristics [7,29].…”
Section: Raman Histologymentioning
confidence: 99%
“…The Raman scattering phenomenon posits that the spontaneous inelastic scattering of light will occur based on the molecular characteristics of the sample [29,30]. Therefore, Raman spectroscopy allows for the rapid, non-destructive acquisition of label-free information directly from the sample's chemical characteristics [7,29]. As most neuropathologies involve alterations at the molecular level, Raman technology has been increasingly efficacious in rapidly diagnosing and treating ischemic or traumatic brain injuries, neurodegenerative diseases, and brain tumors [29].…”
Section: Raman Histologymentioning
confidence: 99%